Complete Shift in Glycosyl Donor Specificity in Mammalian, but not C. elegans β1, 4‐GalT1 Y286L mutants, Enables the Synthesis of N, N‐Diacetyllactosamine. Issue 7 (10th February 2022) - Cao, Ran; Li, Jing‐Xuan; Chen, Huan; Cao, Cui; Zheng, Feng; Huang, Kun; Chen, Ya‐Ran; Flitsch, Sabine L.; Liu, Li; Voglmeir, Josef
Abstract: N, N ‐diacetyllactosamine (LacdiNAc) is a motif present in various glycoconjugates of animal cell surfaces. The enzymatic synthesis of the LacdiNAc motif was previously achieved by using mutant variants of the human and bovine β1, 4‐galactosyltransferase 1 (β1, 4‐GalT1, EC 2.4.1.38). These enzymes bear a specific tyrosine to leucine substitution, which enables the transfer of GalNAc from UDP‐GalNAc. Herein, we present that the same tyrosine to leucine substitution in recombinant β1, 4‐GalT1 orthologues of mouse, rat, or pig also resulted in the complete shift of the glycosyl donor specificity from UDP‐galactose to UDP‐GalNAc. In addition, we tested a previously undescribed β1, 4‐GalT1 orthologue from C. elegans (CeGalT1). Given that this enzyme possesses an isoleucine residue in the wild‐type variant, this enzyme should prefer UDP‐GalNAc as a glycosyl donor substrate. Surprisingly, CeGalT1 was strictly specific for UDP‐Gal, but an isoleucine to tyrosine mutant variant of CeGalT1 widened the substrate range towards UDP‐GalNAc. In addition, the CeGalT1 mutant variant showed also significantly improved enzymatic activity towards UDP‐Gal. To further investigate the role of this tyrosine to leucine substitution of β1, 4‐GalT1 and to evaluate the potential of this mutation for biotechnological applications, we generated Tyr286Leu B4galt1 mice using CRISPR/Cas9 gene editing and screened the milk of these mice for its ability to synthesize N, N ‐diacetyllactosamine. Abstract : Mutations : A complete shift in glycosyl donor specificity from UDP‐galactose to UDP‐N‐acetylgalactosamine was observed in mammalian β1, 4‐galactosyltransferase 1 Y286L mutant orthologs. Surprisingly, mutations of the same amino acid position in the C. elegans β1, 4‐galactosyltransferase 1 ortholog had the contrasting effect on the glycosyl donor specificity.